Humoral response to the BBIBP-CorV vaccine over time in healthcare workers with or without exposure to SARS-CoV-2 - Badano, Maria Noel (2022)
SARS-CoV-2-specific humoral response was analyzed over time in a group of healthcare workers with or without exposure to SARS-CoV-2, who underwent vaccination with BBIBP-CorV (Sinopharm) vaccine in Argentina. Seroconversion rates in unexposed subjects after the first and second doses were 40 % and 100 %, respectively, showing a significant increase in antibody concentrations from dose 1 to dose 2 (p < 0.0001). The highest antibody concentrations were found in younger subjects and women, remaining significantly associated in a multivariable linear regression model (p = 0.005). A single dose of the BBIBP-CorV vaccine induced a strong antibody response in individuals with prior SARS-CoV-2infection, while a second dose did not increase this response. A sharp increase in antibody concentrations was observed following SARS-CoV-2 infection in those participants who became infected after the first and second doses (p = 0.008). Individuals with SARS-CoV-2 exposure prior to vaccination showed significantly higher anti-spike IgG antibody levels, at all-time points, than those not exposed (p < 0.001). Higher antibody titers were induced by a single dose in previously SARS-CoV-2 infected individuals than those induced in naïve subjects by two doses of the vaccine (p < 0.0001). Three months after the second dose both groups showed a decline in antibody levels, being more abrupt in unexposed subjects. Overall, our results showed a trend towards lower antibody concentrations over time following BBIBP-CorV vaccination. Sex and age seem to influence the magnitude of the humoral response in unexposed subjects while the combination of exposure to SARS-CoV-2 plus vaccination, whatever the sequence of the events was, produced a sharp increase in antibody levels. Evaluation of the humoral responses over time and the analysis of the induction and persistence of memory B and T cell responses, are needed to assess long-term immune protection induced by BBIBP-CorV vaccine.